2020
DOI: 10.7759/cureus.11332
|View full text |Cite
|
Sign up to set email alerts
|

Current Surgical Options for Moyamoya Disease

Abstract: Moyamoya disease (MMD) is a cerebrovascular disease of unknown etiology characterized by stenotic and occlusive arterial changes of the anterior circulation, with subsequent proliferative development of arterial collateralization. In spite of there being limited understanding of the clear etiology of MMD, surgical revascularization for MMD is considered the standard treatment to prevent further stroke. While the use of surgical revascularization to prevent future hemorrhagic stroke in MMD is still controversia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 17 publications
0
9
0
3
Order By: Relevance
“…Epidemiological analyses have reported distinctive features of familial Moyamoya disease, with the male to female ratio at 5.0 in familial cases ( 42 ). Surgical treatment constitutes the main available treatment for MMD with no pharmacological options currently available ( 43 ). In a previous study that included 10 years of follow-ups, antiplatelet medications were not found to affect the incidence of cerebral infarction in patients with Moyamoya disease ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological analyses have reported distinctive features of familial Moyamoya disease, with the male to female ratio at 5.0 in familial cases ( 42 ). Surgical treatment constitutes the main available treatment for MMD with no pharmacological options currently available ( 43 ). In a previous study that included 10 years of follow-ups, antiplatelet medications were not found to affect the incidence of cerebral infarction in patients with Moyamoya disease ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…Surgical revascularization has been offered in ischemic MMD to augment cerebral blood flow and prevent future ischemic events. While in hemorrhagic MMD, theoretically, it is believed that bypass procedures prevent the recurrent hemorrhages by lowering the long-term hemodynamic stress on the collateral vasculature [13] . In a study on asymptomatic MMD, 7 of 34 patients suffered an ischemic stroke, TIA, or hemorrhagic stroke, who did not undergo revascularization surgery.…”
Section: Discussionmentioning
confidence: 99%
“…O caso apresentado descreve os eventos isquémicos como forma de apresentação da doença de Moyamoya, resultado da hipoperfusão provocada pela progressiva esteno-oclusão cerebral, o que se traduz num acidente vascular cerebral ou num acidente isquémico transitório. 1,2,4,[7][8][9]11 É importante considerar esta doença no diagnóstico diferencial de adultos jovens com a sintomatologia descrita pelas implicações terapêuticas e de prognóstico associadas. Procedeu-se a revascularização indireta esquerda, apesar do acometimento bilateral das ACIs, por ser a estenose mais grave e pela sintomatologia afásica apresentada inicialmente.…”
Section: Discussionunclassified
“…4 É mais frequente na população do leste asiático 2-8 e a idade de inicio tem uma distribuição bimodal com um pico na primeira década de vida e um segundo pico na quarta década de vida. 2,9 O principal sintoma nos adultos é a hemorragia intracraniana que provoca um acidente vascular cerebral hemorrágico. Nas crianças é mais frequente o acidente vascular cerebral isquémico.…”
Section: Introductionunclassified
See 1 more Smart Citation